1988
DOI: 10.1111/j.1365-2214.1988.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of social interactions between mothers and their disabled infants: a review

Abstract: This paper examines interactional characteristics of disabled infants and young children and their mothers. Interactional characteristics of disabled infants and young children differ from those of non-disabled children in several ways: disabled children provide fewer and less readable cues to the mother; they demonstrate less positive affect, more negative affect, and more muted affect; and they have more difficulties synchronizing turn-taking than non-handicapped children. Maternal interactions with disabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 43 publications
1
22
0
4
Order By: Relevance
“…At moments when this succeeds, both partners seem to perceive and follow each other's actions, and a mutual and playful interaction can be created (Rogers, 1988). In this way, meaningfulness refers to interactions where both partners contribute to the continuation of the interaction because it seems to be meaningful to do just that -even when we cannot know what precise meaning the interaction has for the child.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At moments when this succeeds, both partners seem to perceive and follow each other's actions, and a mutual and playful interaction can be created (Rogers, 1988). In this way, meaningfulness refers to interactions where both partners contribute to the continuation of the interaction because it seems to be meaningful to do just that -even when we cannot know what precise meaning the interaction has for the child.…”
Section: Introductionmentioning
confidence: 99%
“…While often the relative quantity of communicative behaviours increases, it can still be hard for the therapist to interpret and respond to them as such in an ongoing interaction. Analysis of interactions between adults and young handicapped children (among others those with autism and Down's Syndrome) show that even the child's own parents can have problems in understanding responses because of their frequently weak, random, or ambivalent character (see Rogers, 1988 for a review). At worst the problem is twofold: the child shows no sign of understanding the adult's initiative, and the adult cannot read the child's reactions as meaningful because they seem to occur without context.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that, not surprisingly, the learning-disabled children responded less to their mothers' ini tiations and they themselves initiated half as many interactions as did their normal peers within the study. Rogers [5] found that: disabled children provide fewer and less readable cues to the mother; they demon strate less positive affect, more negative affect and more muted affect; and they have more difficulties synchronizing turn taking than non handicapped children. Maternal interac tions with disabled children differ from those of mothers with non disabled children in dimensions involving maternal activity and positive affect.…”
Section: Research Into Parent-child Interactionmentioning
confidence: 99%
“…Gelişimsel yetersizliği olan bebekler ve annelerinin etkileşimsel davranışları, normal gelişim gösteren çocuk ve ebeveynlerine göre farklılık gösterebilmektedir (Rogers, 1988). Gelişimsel yetersizliği olan çocuklar ile ebeveynlerinin etkileşimsel davranışlarını, normal gelişim gösteren çocuklar ve ebeveynlerinin etkileşimsel davranışları ile karşılaştırarak inceleyen ilgili araştırmalarda iki grubun etkileşimsel davranışları arasında farklılıklar olduğu, gelişimsel yetersizliği olan çocukların normal gelişim gösteren çocuklara göre daha az etkileşim başlattıkları ve daha az yanıt verdikleri, gelişimsel yetersizliği olan çocuk annelerinin normal gelişim gösteren çocuk annelerine göre çocuklarını daha fazla yönlendirdikleri (Ceber-Bakkaloğlu ve Sucuoğlu, 2000) ve çocuklarının davranışlarına daha az yanıtlayıcı oldukları bulunmuştur (Mahoney ve Powell, 1988).…”
unclassified